"No more than one day per week" seems simple enough: So why is conflict of commitment so confusing?. (18th May 2020) - Samsa, Gregory
ABSTRACT: Conflict of interest (COI) and conflict of commitment (COC) are similar in that both concern the "risk that professional judgment or actions regarding a primary interest will be unduly influenced by a secondary interest" (Institute of Medicine). The Institute of Medicine recommends that the circumstances, risks, and evaluative frameworks for COI and COC warrant separate consideration. Here, we discuss some principles (and thus an evaluative framework) underlying COC and hope to provide a clarifying framework which extends across institutions. We propose that: An institution should become concerned about relationships, whether considered individually or as a whole, which because of the amount of the time commitment and/or the amount of the monetary compensation, potentially induces a dual loyalty or otherwise calls into question the ability of the faculty member to discharge their primary responsibility to the institution. The impact of single relationships on single actions constitutes COI; the net impact of multiple relationships and/or the overall ability to fully discharge primary institutional responsibilities constitutes COC.